Study of Thermal Performance of Vaccum-Tube for Solar Water Heaters Adapted for Peruvian Coastal Scenario (SCIÉNDO INGENIUM, 2025)
The present research aimed to theoretically determine the arrangements of evacuated tubes, considering both tilt angle and inter-tube spacing, that maximize the total annual energy collection for five Peruvian coastal cities. The parameters considered included tube dimensions, azimuthal orientation, tilt angle, and inter-tube spacing. To perform a parametric study of the total solar energy captured by a single evacuated tube, varying the tilt angle for each of the 365 days of the year, the spacing between tubes, and the geographic location of five coastal Peruvian cities, a mathematical model was implemented in Matlab/Octave. The results show that maximum solar energy collection is achieved with tilt angles between 0° and 15° and a relative spacing between tubes equal to twice the outer diameter. Furthermore, it was demonstrated that the optimal operating tilt angles of evacuated tubes depend on the specific city in which they are installed. Unlike commercial systems, tubes arranged at a 15° tilt can capture greater amounts of energy without compromising their thermal conversion through the thermosiphon effect.
Keywords: Solar Energy; Vacuum-Tube Solar Water Heater; Tilt Angle; Geographical Location